Social disparity and oral health - Navarro, Maria Fidela de Lima; Modena, Karin Cristina da Silva; Bresciani, Eduardo [UNESP] (FapUNIFESP (SciELO), 2012)
There is a clear reported association between social disparity and oral health, for example, between dental caries and malnutrition in children. This fact is detected in several studies, and also found amongst the Brazilian population. However, several efforts have been made to improve the quality of life of the population and to achieve the 2015 Millennium Development Goals. Oral health is a branch to be improved among these goals. The Brazilian experience has been drawing the attention of authorities, insofar as there have been direct improvements in oral health through state oral health programs, and also indirect results by improving the quality of life of the population. Included within the Brazilian oral health programs are the Family Health Program and Smiling Brazil Program. The former is a global healthcare program which involves primary oral healthcare, while the latter is a specialized oral care program. Among the social programs that would indirectly improve oral health are Family Stipend and the Edmond and Lily Safra International Institute of Neuroscience of Natal (ELS-IINN). In conclusion, although oral health problems are related to socioeconomic factors, the implementation of primary oral health programs and programs to improve the population's quality of life may directly or indirectly improve the oral health scenario. This fact is being observed in Brazil, where the oral health policies have changed, and social programs have been implemented.
Keywords: Dental caries; Malnutrition; Oral health; State dentistry; Brazil; child; dental procedure; health; health care policy; health disparity; human; organization and management; public health; socioeconomics; Child; Dental Care for Children; Health Policy; Health Status Disparities; Humans; National Health Programs; Oral Health; Socioeconomic Factors